Neuroprotective Effects of Nano-Curcumin against Cypermethrin Associated Oxidative Stress and Up-Regulation of Apoptotic and Inflammatory Gene Expression in Rat Brains - Mohammad Ashafaq; Sohail Hussain; Saeed Alshahrani; Rahimullah Siddiqui; Mohammad Intakhab Alam; Manal Mohamed Elhassan Taha; Yosif Almoshari; Saad S. Alqahtani; Abdulmajeed M. Jali; Hashim M. Aljohani (MDPI AG, 2023)
Cypermethrin (CPM) is the most toxic synthetic pyrethroid that has established neurotoxicity through oxidative stress and neurochemical agitation in experimental rats. The toxic effects are supposed to be mediated by modifying the sodium channels, reducing Na-K ATPase, acetylcholine esterase (AchE), and monoamine oxidase (MAO). The use of curcumin nanoparticles (NC) that have potent antioxidant, anti-inflammatory and antiapoptotic properties with improved bioavailability attenuates neurotoxicity in rat brains. To test this hypothesis, animals were divided into five groups, each having six animals. Group-I control received vehicle only, while Group-II was treated with 50 mg/kg CPM. Group-III and Group-IV received both CPM and NC 2.5 mg/kg and 5 mg/kg, respectively. Group-V received 5 mg of NC alone. The CPM and NC were given by oral route. Afterwards, brain antioxidant status was measured by assessing lipid peroxidation (LPO), 4-HNE, glutathione reduced (GSH), antioxidant enzyme catalase, and superoxide dismutase (SOD) along with neurotoxicity markers Na-K ATPase, AchE, and MAO. Inflammation and apoptosis indices were estimated by ELISA, qRT-PCR, and immunohistochemistry, while morphologic changes were examined by histopathology. Observations from the study confirmed CPM-induced neurotoxicity by altering Na-K ATPase, AchE, and MAO, and by decreasing the activity of antioxidant enzymes and GSH. Oxidative stress marker LPO and the level of inflammatory interleukins IL-6, IL-1β, and TNF-α were notably high, and elevated expressions of Bax, NF-kB, and caspase-3 and -9 were reported in CPM group. However, NC treatment against CPM offers protection by improving antioxidant status and lowering LPO, inflammation, and apoptosis. The neurotoxicity marker's enzyme successfully attenuated after NC treatment. Therefore, this study supports the administration of NC effectively ameliorated CPM-induced neurotoxicity in experimental rats.